Przestrzeń domagająca się działania. Wokół aktualnych wyzwań animacji społecznej - Retmaniak, Stanisława (Pedagogika Społeczna Nova, 2026)
The author highlights the challenges facing social animation posed by crises created by humans and their dominance. She argues that traditional approaches, focused solely on humans, are insufficient in a posthuman world. She proposes a transversal approach to social pedagogy and animation, which includes non-human entities as active participants in the formation of emergent communities. The author expands the reflection on social animation in a transversal dimension by incorporating a posthumanist perspective, recognizing the influence of space and place on individuals and communities.